(untitled) (Journal of the College of Basic Education, 2022)
The study concluded that the topographic, climatic and geological characteristics are the main reason for the occurrence of landslides supported by natural factors that the region is exposed to such as the occurrence of moderate-intensity earthquakes, the activity of chemical weathering, the work of waterways and the increase in slope loads resulting from the accumulation of snow during the winter season and other human factors represented by the increase in road construction And the construction of engineering facilities and the accompanying removal of natural vegetation, undermining the base of slopes and increasing loads. The geographical distribution of all types of landslides concentrated in particular to the east and south of the study area.